1996
DOI: 10.1104/pp.112.1.207
|View full text |Cite
|
Sign up to set email alerts
|

13C Nuclear Magnetic Resonance Detection of Interactions of Serine Hydroxymethyltransferase with C1-Tetrahydrofolate Synthase and Glycine Decarboxylase Complex Activities in Arabidopsis

Abstract: ~~ ~~ I n C, plants, serine synthesis is associated with photorespiratory glycine metabolism involving the tetrahydrofolate (THF)-dependent activities of the glycine decarboxylase complex (CDC) and serine hydroxymethyl transferase (SHMT). Alternatively, THF-dependent serine synthesis can occur via the C1 -THF synthase/SHMT pathway. We used 13C nuclear magnetic resonance to examine serine biosynthesis by these two pathways i n Arabidopsis fhaliana (L.) Heynh.Columbia wild type. We confirmed the tight coupling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 26 publications
2
60
0
Order By: Relevance
“…It has been proposed that the mitochondrial Gly-to-Ser conversion, by recycling Gly originating from extramitochondrial SHM reactions, represents an obligatory component of onecarbon metabolism not only in photosynthetic but in all plant tissues (Mouillon et al, 1999). On the other hand, a GDC-independent pathway for the supply of CH 2 -THF, driven by the C1-THF synthase system, has been suggested as an important means of compensating for the lack of GDC activity (Prabhu et al, 1996;Wingler et al, 1999;Li et al, 2003). The existence of such pathways will be difficult to prove because of the very early developmental arrest of the GDC-lacking double mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that the mitochondrial Gly-to-Ser conversion, by recycling Gly originating from extramitochondrial SHM reactions, represents an obligatory component of onecarbon metabolism not only in photosynthetic but in all plant tissues (Mouillon et al, 1999). On the other hand, a GDC-independent pathway for the supply of CH 2 -THF, driven by the C1-THF synthase system, has been suggested as an important means of compensating for the lack of GDC activity (Prabhu et al, 1996;Wingler et al, 1999;Li et al, 2003). The existence of such pathways will be difficult to prove because of the very early developmental arrest of the GDC-lacking double mutant.…”
Section: Resultsmentioning
confidence: 99%
“…It shall be noted that residual GDC activity has been reported for such mutants (for example, Li et al, 2003). Moreover, it was reported that CH 2 -THF and Ser can be synthesized through multiple routes including the so-called C1-THF synthase/SHM pathway (Prabhu et al, 1996;Li et al, 2003). In this GDC-bypassing pathway, formate would be converted into CH 2 -THF via two enzymes, 10-formyl-THF synthetase and the bifunctional enzyme CH 2 -THF dehydrogenase/ CH 2 -THF cyclohydrolase.…”
mentioning
confidence: 99%
“…5,10 methylene tetrahydrofolate is also produced by glycine decarboxylase activity which is then used as the main single carbon donor for synthesis of serine (73). Yet, the synthesis via the 10-formyltetrahydrofolate synthetase provides independent 5,10 methylene tetrahydrofolate for the synthesis of serine (74). Interestingly using 13 C nuclear magnetic resonance, interactions among serine hydroxymethyltransferase, tetrahydrofolate synthase, and glycine decarboxylase complex activities were shown (74).…”
Section: Clustering Reveals Responses That Are Dependent On the Trophmentioning
confidence: 99%
“…In [a-13 C]Gly labeling experiments of whole Arabidopsis thaliana, only labeled Gly and Ser accumulated, indicating that Gly is not converted directly to Thr by Thr aldolase in vivo (Prabhu et al, 1996(Prabhu et al, , 1998. Metabolite profiling of Medicago truncatula cell cultures showed that the production of Gly from Thr, likely by Thr aldolase, is induced by treatment with methyl jasmonate (Broeckling et al, 2005).…”
Section: Introductionmentioning
confidence: 99%